Anderson‐Localization and the Mott–Ioffe–Regel Limit in Glassy‐Metallic PEDOT. (25th April 2017) - Farka, Dominik; Coskun, Halime; Gasiorowski, Jacek; Cobet, Christoph; Hingerl, Kurt; Uiberlacker, Lisa Maria; Hild, Sabine; Greunz, Theresia; Stifter, David; Sariciftci, Niyazi Serdar; Menon, Reghu; Schoefberger, Wolfgang; et al.
Abstract : Conductive polymers represent a rare case in which free‐carrier absorption is shifted to the far‐infrared—an attractive advantage in light of the requirement of highly transparent conductors across the visible and near‐infrared. Unfortunately, prior approaches to doping these polymers—imperative for high conductance—have consistently led to strong localization arising from fluctuating band alignment among polymer chains. Here, this study overcomes this problem of doping‐induced Anderson localization for the first time in polymers by developing a new conductive polymer synthesis strategy. This study achieves polymerization and doping simultaneously, thereby using an alternative nonmetal oxidant and thereby avoiding the introduction of excess energy that normally arises from exergonic polymerization. The resulting conductive polymer is the first to provide electron coherence in a metallic polymer thin film. The conductivity reaches a remarkable 3300 S cm −1 at 1.8 K and the mean electron scattering length a record 330 Å. This enhancement drives the glassy metal transition in the vicinity of the Mott–Ioffe–Regel (MIR) limit. The new metallic polymer achieves 10 −2 Ω −1 figure of merit, making it a contender for transparent conductive contacts previously only accessible using inorganics. The new material offers a uniquely broad transparency window spanning the UV to the mid‐infrared. Abstract : Magnetic‐field‐induced electron resonance increases the electrical conductivity in the metallic state of conductive polymers. Evidenced in one‐step synthesized vapor‐cast thin film, such a metallic polymer offers great potential as alternative transparent electrode. Conductivities beyond 4000 S cm −1 and transparency spanning the UV to infrared result in a metal‐free transparent conductor.